The drivers of non-adherence to albuminuria testing guidelines and the clinical and economic impact of not identifying chronic kidney disease - Groehl, F; Garreta-Rufas, A; Meredith, K; Harris, J; Rossing, P; Hobbs, FDR; Wanner, C (Dustri-Verlag, 2023)
Background: Regular monitoring is required to ensure that patients who have, or are at risk of, chronic kidney disease (CKD) receive appropriate management. Guidelines recommend regular testing of estimated glomerular filtration rate (GFR) and albuminuria. However, evidence suggests that albuminuria testing rates, specifically urine albumin-to-creatinine ratio (UACR), are suboptimal.